An experimental study on bond behavior of tensile lap spliced FRP in aggressive environments. (August 2021) - Toufigh, Vahab; Haghighi, Sina; Kosarimovahhed, Mohammadhossein
Abstract: This paper investigates the tensile performance of single lap-spliced fiber reinforced polymer (FRP) coupons subjected to harsh environments. Uniaxial tensile tests were performed on 945 specimens after 2, 4, 12, 20, 28, 36, and 48 weeks of exposure to various conditions, including acidic, alkalis, distilled water, and seawater solutions. The experiment results indicated that a solution with a pH of 12.5 had the highest impact on the deterioration of all joints, regardless of the FRP type and bond length. The bond strength reduction was approximately 18% in glass specimens exposed to the acidic solution and less than 10% in aramid specimens. Joints made of carbon showed excellent resistance against all the conditions. The change in failure mode and the minimum lap splice length were investigated for different types of FRPs. Finally, the effects of parameters on the bond strength of FRP were statistically analyzed using ANOVA analysis, and recommendations for minimum lap splice length were presented based on the analyzed data.